INFLUENCE OF PLANT GROWTH REGULATORS ON SEED YIELD, QUALITY AND STORABILITY OF SINGLE CROSS MAIZE HYBRID GH-0727 GH-07 - GOVINDA; R. B. JOLLI (The Bioscan, 2018)
A field experiment was conducted during kharif2015 at the Main Agricultural Research Station (Saidapur Unit), UAS, Dharwad to study the influence of plant growth regulators on field performance and yield in maize hybrid GH-0727.Among the plant growth regulator treatments, GA3 (50 ppm) + IBA (100 ppm) recorded significantly higher plant height at harvest (203.33 cm), SPAD value (56.24) with minimum number of days to 50 percent tasseling and silking (53 and 57.33 days, respectively). The treatment, GA3 (50 ppm) + IBA (100 ppm) also resulted in higher cob length (16.60 cm), cob girth (13.46 cm), number of rows per cob (17.33), number of seeds per row (29.33),yield per plant (72.37g), test weight (28.03 g), yield per ha (24.87 q/ha)and shelling per cent (83.66), which was on par with GA3 (75 ppm) + IBA (125 ppm).During storage, higher germination per cent (98.05 and 97.25) and field emergence( 90.60 and 89.70 ) were recorded at first and second months of storage period and significantly higher seedling vigour index (3092, 2874 and 2493) was recorded at first, second and third month of storage period with the treatment which received GA3(50 ppm) + IBA (100 ppm).